2017
DOI: 10.1103/physrevb.96.094424
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the inverse spin Hall effect in the topological crystalline insulator SnTe using spin pumping

Abstract: Topological crystalline insulator SnTe is a promising material for future spintronics applications because of the strong spin-orbit coupling and surface states protected by the mirror symmetry of the crystal. In this paper, using a high-quality epitaxial ( 001)-oriented Fe/SnTe/CdTe/ZnTe heterostructure grown on GaAs, we successfully observe the inverse spin Hall effect in SnTe induced by spin pumping, which is confirmed by detailed analyses of the dependence of the electromotive force on the microwave power, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…However, the polar distortions of SnTe are suppressed already at 0.02|e|/u.c., thus the giant spin Hall effect should rather be attributed to the paraelectric phase. In fact, the estimated spin Hall angle is in good agreement with the experimental value of 0.01 measured in the high-temperature rocksalt structure by Ohya et al 24 Although it has been suggested that the topological surface states could enhance the efficiency of spin Hall effect, our analysis shows that the large spin Hall angle can be entirely assigned to the strong SOC of bulk electronic states in the cubic structure. Thus, despite the realization of FERSC seem difficult in this material, it is extremely promising for spintronics applications based on spin Hall effect.…”
Section: Spin Hall Effect In Doped Ferscsupporting
confidence: 91%
See 1 more Smart Citation
“…However, the polar distortions of SnTe are suppressed already at 0.02|e|/u.c., thus the giant spin Hall effect should rather be attributed to the paraelectric phase. In fact, the estimated spin Hall angle is in good agreement with the experimental value of 0.01 measured in the high-temperature rocksalt structure by Ohya et al 24 Although it has been suggested that the topological surface states could enhance the efficiency of spin Hall effect, our analysis shows that the large spin Hall angle can be entirely assigned to the strong SOC of bulk electronic states in the cubic structure. Thus, despite the realization of FERSC seem difficult in this material, it is extremely promising for spintronics applications based on spin Hall effect.…”
Section: Spin Hall Effect In Doped Ferscsupporting
confidence: 91%
“…23 Finally, recent spin pumping experiments performed for the high-symmetry paraelectric bulk revealed strong spin Hall effect whose origin remains elusive. 24 Our calculations based on density functional theory (DFT) allowed us to quantitatively estimate spin Hall conductivities (SHC) for low-and high-symmetry structures of both materials. First, we have unveiled that the ferroelectric phase could indeed enhance the spin Hall effect as compared with the paraelectric structure.…”
Section: Introductionmentioning
confidence: 99%
“…2a ). Here, ρ is the resistivity of LSMO and n is 1–2 33 . Therefore, the influence of the galvanomagnetic effects is negligibly small.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, SHE has been achieved in bulk β−SnTe which suggests that its successful realization in 2D phase is very probable. 45 Despite the values of doping/strain required to reach/tune the giant SHC might seem large, the actual 2D character of these compounds can greatly help to overcome these difficulties. For example, different stacking order or thickness of the multilayer might reduce the required doping or the Fermi level could be additionally shifted by any charge originating from a substrate, 46 or any additional strain could result from lattice constant matching at the interface.…”
Section: Discussionmentioning
confidence: 99%